Pastoral implications of Biblical theology : truths that compelled. - Lawton, Stewart (New York : Seabury Press, 1968)
London ed. (Hodder and Stoughton) has titles: Truths that compelled; contemporary implications of Biblical theology.
Keywords: Bible -- Theology; Bible -- Criticism, interpretation, etc. -- History